Comparison of device‐specific adverse event profiles between Impella platforms. Issue 12 (16th September 2020) - Chen, Stacey; Paone, Darien; Spellman, Lilly; Ranganath, Neel K.; Carillo, Julius A.; Gidea, Claudia G.; Reyentovich, Alex; Thompson, Craig A.; Razzouk, Louai; Kon, Zachary N.; Moazami, Nader; Smith, Deane E.
Abstract: Background: The Impella (Abiomed) ventricular support system is a family of temporary mechanical circulatory support (MCS) devices used to treat patients with cardiogenic shock, acute cardiogenic decompensation, and for high‐risk percutaneous or surgical revascularization. These devices include the percutaneously implanted 2.5/cardiac power (CP) and the surgically implanted 5.0/left direct (LD). Despite the beneficial effects and increased usage of these devices, data to assess adverse outcomes and guide clinician decision‐making between the Impella CP and 5.0/LD are limited. Methods: This is a retrospective analysis of 91 consecutive patients who required at least 24 h of Impella support, from January 1, 2015 to December 31, 2019. Groups were stratified based on either initial Impella CP or 5.0/LD placement. Clinical outcomes and in‐hospital complications were compared. Results: Impella CP was implanted in 66 patients (mean age: 61 ± 15 years, male 71.2%) and Impella 5.0/LD was implanted in 25 patients (mean age: 62 ± 9 years, male 84.0%). There was greater stability of device position ( p  = .033), less incidence of hemolysis ( p  < .001), and less frequent need for additional MCS ( p  = .001) in patients implanted with the Impella 5.0/LD compared with Impella CP in this study cohort. Patients with Impella 5.0/LD were more likely to survive from Impella and survive to discharge. Conclusions: This study suggests that for patients who require temporary MCS for more than 24 h, the Impella 5.0/LD may have a more favorable device‐specific adverse profile compared with the Impella CP.